Dietary intake, biological status, and barriers towards omega-3 intake in elite level (tier 4), female athletes: Pilot study - Hooks, M. P.; Madigan, S. M.; Woodside, J. V.; Nugent, A. P. (Nutrients, 2023)
Omega-3 polyunsaturated fatty acids (n-3 PUFA) have unique properties which benefit athlete populations. The literature investigating NCAA collegiate, rugby sevens and German endurance athletes indicates suboptimal n-3 PUFA dietary intake and biological status. The aims of this study were: (i) to explore the dietary intakes and FA profiles of elite level, team-based, female athletes and (ii) to understand perceived barriers towards achieving n-3 dietary guidelines. A total of 35 athletes (24.8 ± 4.5 years) completed both a questionnaire and a finger prick test. All the participants reported consuming fish and seafood over the previous six months however only nine athletes consumed = 2 servings of fish per week. Four participants reported using an n-3 supplement. The mean omega-3 index (O3I; including supplementers) was below target levels of >8% (5.19 ± 0.86%). O3I was significantly higher (p < 0.001) in those consuming = 2 servings of fish per week and/or supplements (5.91 ± 0.81%) compared with those who did not (4.82 ± 0.63%). The main barriers reported by those not consuming two servings of fish per week were sensory (n = 11; 42%), cooking skills (n = 10; 38%) and knowledge of n-3 benefits (n = 7; 27%). The current study shows that elite level female athletes present with suboptimal n-3 dietary intake and O3I due to their food preferences, cooking skills and n-3 knowledge.